PENGARUH PAJAK, MEKANISME BONUS, UKURAN PERUSAHAAN, KEPEMILIKAN ASING, DAN TUNNELING INCENTIVE TERHADAP TRANSFER PRICING (Perusahaan Sektor Industri Dasar Dan Kimia Yang Listing Di BEI Tahun 2011-2014) - Thesa Refgia; Vince Ratnawati; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Transfer pricing is a result of business growth business today. National companies now become the multinational corporations whose activities are not only centered on one country alone, but in some countries. This is done for tax evasion in order to obtain high profits. The purpose of this study to examine the effect of tax, bonus mechanism, firm size, foreign ownership and tunneling incentive to transfer pricing in the company's chemical and basic industry sectors listed on the Indonesia Stock Exchange in 2011-2014. These samples were obtained by purposive sampling method using several criteria in order to obtain a sample of 13 companies. Hypothesis testing is done by linear regression models with SPSS 16. The result shows that tax have significant effect on transfer pricing at 0.049 < 0.050 level of significance, foreign ownership have significant effect on transfer pricing at 0.044 < 0.050 level of significance, and tunneling incentive have significant effect on transfer pricing at 0.005 < 0.050 level of significance, the mechanism of bonuses doesn’t take any effect on transfer pricing at 0.757 > 0.050 level of significance and company size doesn’t take any effect on transfer pricing at 0.427 > 0.050 level of significance. The amount of determination (r2) of the tax effect, the mechanism of bonuses, company size, foreign ownership and tunneling incentive to transfer pricing that is equal to 27.2%, while the remaining 72.8% is influenced by other variables not examined in this study.Keywords: Taxes, Mechanism Bonus, Company Size, Foreign Ownership Incentive And Tunneling Against Transfer Pricing.